Bauran Pemasaran Jasa, Citra, dan Kepuasan Mahasiswa: Sebuah Kajian Perguruan Tinggi Swasta di Kediri - Aliami, Sri; Hakimah, Ema Nurzainul (Efektor, 2020)
Business in education can be classified as a service business. The main principle to run this type of business is to develop and maintain the trust of society as well as to give satisfaction value through various strategies. Based on the fact universities must be able to manage the available resources to fulfill the students’ expectations. The objective of this study is to analyze the effect of the service marketing mix and image of higher education on partial and simultaneous satisfaction. Service marketing mix in this research cover product, price, place, promotion, people, physical evidence, and process. At the same time, the indicators of an image are reputation, tradition, and the identity of a university. Students’ satisfaction can be identified by their desire to reuse the product, the level of file a complaint, giving recommendations to other consumers, the pride of using the product, and obey the regulations. The population is the students of the University of Nusantara PGRI Kediri. The sample total of 81 students using the technique proportional stratified sampling. Used a questionnaire to collect the data and analyzed using multiple linear regression. The Results of the research proved that service marketing mix and image influence significantly in both partial and stimulant towards the satisfaction.